Improved Family Coping Caring for Autistic Disorder Children with Knowledge Education: A Cross-Sectional Study - Setyoadi, Setyoadi; Dwioktaviani, Indri Putri; Ahsan, Ahsan (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2023)
Background: Cognitive, communication, social interaction, behavior patterns, and activity limitations in autistic children become a source of stress for parents. Parents' negative assessment of autistic children leads to maladaptive coping and results in inappropriate parenting behavior. Objective: This study focuses on evaluating parents' knowledge of autistic disorders and their relationship to coping in caring for children with autism. Method: Cross-sectional study is the design of this study. Involving 22 respondents, namely parents of children with autism whose children attend education at Special Schools (SLB) in Malang City. The data collection instrument was developed based on the Knowledge about Childhood Autism Among Health Workers (KCAHW) questionnaire to obtain data on family knowledge variables. Family coping variables using McCubbin's F-COPES questionnaire. Both questionnaires are tools that have been tested for reliability. Analystsare statisticians using the Spearman Rank test with a significance of 5%. Results: 64% of Parisipans had high knowledge of autism and 14% of parents had maladaptive coping. The results of statistical tests found that the level of knowledge about autism was related to family coping mechanisms in children with autisme disorder (p-value 0.003; r 0.599). Conclusion: Adaptive coping of families with autistic disorder children increases with good parental knowledge. Therefore, health education about autism and its care is always informed to the public to prevent maladaptive coping in the care of children with autism disorders in the family. Latar belakang: Keterbatasan kognitif, komunikasi, interaksi sosial, pola perilaku, dan aktivitas pada anak autis menjadi sumber stres bagi orang tua. Penilaian negatif orang tua terhadap anak autis menyebabkan koping maladaptif dan berdampak pada perilaku pengasuhan yang tidak tepat. Tujuan: Penelitian ini berfokus pada evaluasi pengetahuan orang tua tentang gangguan autis dan hubungannya dengan koping dalam merawat anak autisme. Metode: Studi cross sectional merupakan rancangan penelitian ini. Melibatkan 22 responden, yaitu orang tua dari anak dengan Autis yang anaknya mengikuti Pendidikan di Sekolah Luar Biasa (SLB) di Kota Malang. Instrument pengumpulan data dikembangkan berdasarkan kuesioner Knowledge about Childhood Autism Among Health Workers (KCAHW) untuk memperoleh data variabel pengetahuan keluarga. Variabel koping keluarga menggunakan kuisioner F-COPES McCubbin. Kedua kuesioner tersebut merupakan alat yang sudah diuji reabilitasnya. Analisis statistik menggunakan Rank Spearman test dengan signifikansi 5%. Hasil: Partisipan sebanyak 64% memiliki pengetahuan yang tinggi tentang gangguan autism dan masih terdapat orang tua yang memiliki koping maladaptif 14%,. Hasil uji statistik menemukan bahwa tingkat pengetahuan tentang autisme berhubungan dengan mekanisme koping keluarga pada anak dengan gangguan autisme (p-value 0,003; r 0,599). Simpulan: Koping adaptif keluarga yang memiliki anak gangguan autis meningkat dengan pengetahuan orang tua yang baik. Edukasi tentang autisme dan perawatannya perlu selalu diinformasikan kepada masyarakat untuk mencegah koping maladaptif dalam perawatan anak dengan gangguan autisme di keluarga.